Evaluation of thermal behavior and chromatographic characterization of oil extracted from seed of Pittosporum undulatum - Kobelnik, Marcelo; Fontanari, Gustavo Guadagnucci; Ribeiro, Clóvis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP] (Springer Nature, 2018)
The composition of the oil extracted from sweet pittosporum was studied by chromatography analyses. The sweet pittosporum (Pittosporum undulatum) is native to eastern parts of Australia. It is a tree growing to 15 m tall with wavy (undulating) leaf edges and also has attractive fragrant flowers, sweet pittosporum and is found in southern Brazil. The chromatographic profile of this oil reveals a predominance of unsaturated fatty acids, in particular, 28.86% of cis-11-eicosenoic acid (C20:1), 31.44% of eicosatrienoic acid (C20:3n3), 6.61% of docosahexaenoic acid (C22:6n3) and 24.32% of oleic acid (C18:1n9). This oil was characterized by differential scanning calorimetry (DSC), from 100 to − 80 °C and subsequently heated from − 80 °C up to 100 °C, both at cooling/heating rate of 1 and 10 °C min−1. Thermogravimetry (TG) and differential thermal analysis (DTA) in nitrogen and oxygen purge gases under different heating rates show oil stability. The analysis carried out by DSC indicates that this oil has two crystallization peaks under cooling condition. Simultaneous TG–DTA curves show that the behavior of this oil shows variation among the heating rates, with a sudden combustion. The kinetic behavior showed the relationship between the uses of two sample masses, with good parameter and high correlation coefficients (r).
Keywords: Chromatographic analysis; Sweet pittosporum oil; Thermal behavior